2021
DOI: 10.1016/j.jvscit.2021.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Superselective intranidal delivery of platinum-based high-density packing coils for treatment of arteriovenous malformations

Abstract: Arteriovenous malformations (AVMs) classically feature an intervening nidus of poorly differentiated endothelium. The pillar of modern AVM treatment is intranidal delivery and deposition of various liquid embolic agents such as n-butyl cyanoacrylate, ethylene vinyl alcohol copolymer, and ethanol. These agents are cumbersome to prepare, deliver, and deploy and have been associated with complications related to limited delivery control, nonretrievability, frequent microcatheter exchanges, and nontarget embolizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 12 publications
0
0
0
Order By: Relevance
“…Consequently, platinum coils must adapt to confront these emerging challenges associated with flexibility and packing density. Recent studies have showed the flexibility of new generation of bare platinum coils, striking a balance between flexibility due to their uncoated design and robust packing capability [19,20]. Indeed, coil flexibility enables better coiling and packing of vascular anomalies, even in complex access scenarios.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, platinum coils must adapt to confront these emerging challenges associated with flexibility and packing density. Recent studies have showed the flexibility of new generation of bare platinum coils, striking a balance between flexibility due to their uncoated design and robust packing capability [19,20]. Indeed, coil flexibility enables better coiling and packing of vascular anomalies, even in complex access scenarios.…”
Section: Discussionmentioning
confidence: 99%